Analisis SCP (Structure, Conduct, Performance) Jeruk Siam Saat Pandemi Covid-19 di Kecamatan Umbulsari Kabupaten Jember - Habibah, Aisyah Nurma; Yasin, Moh. (Program Studi Agribisnis, 2022)
Siamese oranges in Umbulsari District are citrus fruit production centers in Jember Regency. Therefore, this study aims to determine the structure, behavior and performance of the citrus fruit market in the District of Umbulsari. The analysis used is descriptive analysis with the SCP approach. The analysis of market structure looks at the number of market participants, product differentiation, market information, barriers to market entry and exit and market concentration ratios. In the analysis of market behavior look at the pricing system of each marketing channel and price correlation. The results of the research show that the market structure in Umbulsari District leads to an oligopsony market. In market behavior, there are 3 marketing channels, the position of farmers as price takers and middlemen as price makers, the correlation value of grade A is 0.942 and grade B is 0.764, close to zero, so the relationship between prices at the two market levels is less close. Market performance shows that marketing channel I is the most efficient, but based on field results in Umbulsari District, marketing channel III is the most dominated by farmers.